Pelayanan Referensi Era Milenial di Perpustakaan Perguruan Tinggi: Perspektif Perubahan Sosial Pengguna Perpustakaan - Verry Mardiyanto; Reza Syafrizal (Jurnal Pustaka Ilmiah, 2021)
This study describes contemporary reference services in college libraries with a written perspective on social changes that exist in millennial users or users today. This study also explains the current innovation of reference services in the sample library samples discussed. Examples of library reference services discussed are retrieving information on library pages at IPB, UPI and UNAIR libraries. The research method used is a qualitative research method with a descriptive approach by online observation by taking information on the library website page. The analysis was carried out using online observation on the library website which focuses on observation in the context of reference services. Furthermore, a comparison with social theory is carried out on three types of radical social change in the literature on young users of the digital era. The results in this paper are that these three types of changes can be used as a contextual analysis of the scope of young users or millennial users in determining policies on innovation implemented in library reference services. Information technology innovation by making reference service applications that run on desktop and mobile is one of the current innovations that are right on target and in accordance with current library users. This is evidenced by the increasing number of library service applications so that libraries can innovate in collaboration with mobile or desktop reference services.